PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN TRUTH AND DARE KELAS V SDS MUHAMMADIYAH 3 AL-HILAL TARAKAN - Nasrudin Nasrudin; Kartini Kartini; Dedi Kusnadi (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2020)
This study aims to develop learning media for truth and dare games and find out the appropriateness and level of student interest in learning media developed in thematic class V SDS Muhammadiyah 3 Al-Hilal Tarakan. The development model used refers to the development stage proposed by Sugiono. Data collection instruments used were, interviews, validation sheets and student interest questionnaires.The validation results obtained from material experts amounted to 84%, media experts 85.7% and practitioners 100%. The results of the student interest questionnaire on the initial product trial were 98.6% and the use trial was 99.6%. The results of the validation of material experts, media experts and practitioners indicate that the truth and dare game learning media are very appropriate to be used in the learning process. The results of the questionnaire of interest in the initial product trial and trial use show that the level of student interest in the truth and dare game learning media is in the very interested category.